Determination of lard in mixture of body fats of mutton and cow by fourier transform infrared spectroscopy - Jaswir, Irwandi; Mirghani, Mohamed Elwathig Saeed; Hassan, Torla; Mohd Said, Mohd Zaki (Japan Oil Chemists' Society, 2003)
Fourier transform infrared (FTIR) spectroscopy provides a simple and rapid means of detecting lard blended with chicken, lamb, and cow body fats. The spectral bands associated with chicken, lamb, and cow body fats and their lard blends were recorded, interpreted, and identified. Qualitative differences between the spectra are proposed as a basis for differentiating between the pure animal fats and their blends. A semiquantitative approach is proposed to measure the percent of lard in blends with lamb body fat (LBF) on the basis of the frequency shift of the band in the region 3009–3000 cm−1, using the equation y = 0.1616x + 3002.10. The coefficient of determination (R2) was 0.9457 with a standard error (SE) of 1.23. The percentage of lard in lard/LBF blends was also correlated to the absorbance at 1417.89 and 966.39 cm−1 by the equations y = 0.0061x + 0.1404 (R2 = 0.9388, SE = 0.018) and y = 0.004x + 0.1117 (R2 = 0.9715, SE = 0.009), respectively. For the qualitative determination of lard blended with chicken body fat (CF), the FTIR spectral bands in the frequency ranges of 3008–3000, 1418–1417, 1385–1370, and 1126–1085 cm−1 were employed. Semiquantitative determination by measurement of the absorbance at 3005.6 cm−1 is proposed, using the equation y = 0.0071x + 0.1301 (R2 = 0.983, SE = 0.012). The percentage of lard in lard/GF blends was also correlated to the absorbance at 1417.85 cm−1 (y = 0.0053x + 0.0821, with R2 = 0.9233, SE = 0.019) and at 1377.58 cm−1 (y = 0.0069x + 0.1327, with R2 = 0.9426, SE = 0.022). For blends of lard with cow body fat (CBF) bands in the range 3008–3006 cm−1 and at 1417.8 and 966 cm−1 were used for qualitative detection. The equation y = –0.005x + 0.3188 with R2 = 0.9831 and SE = 0.0086 was obtained for semiquantitative determination at 966.22 cm−1. Paper no. J9636 in JAOCS 78, 753–761 (July 2001).